Impacts of potassium permanganate (KMnO4) catalyst on properties of hydrogen peroxide (H2O2) foamed porous cement slurry. (15th May 2016) - Wang, Zhenjun; Liu, Liang; Zhou, Junxiang; Zhou, Changjun
Abstract: The foaming performance of porous cement slurry (PCS) foamed by H2 O2 was greatly affected by types and dosages of catalysts. In this paper, KMnO4 was adopted as catalyst to the H2 O2 foamed PCS. The influences of the catalyst were investigated through the apparent density and coefficient of thermal conductivity (CTC) of each H2 O2 foamed PCS under different water to cement ratios (w/c ratios). The catalyst's contribution degree to foaming effect (CDFE) in cement slurry was compared to the control group. The geometrical factors of pores in PCS were obtained through digital image processing technique. Morphology and components of PCS were analyzed with Scanning Electron Microscope and X-ray Diffraction, respectively. The results show that KMnO4 can exert excellent catalytic effect in H2 O2 foamed PCS. The Portland cement in PCS can hydrate as normal. KMnO4 displays higher contribution degree to foaming effect for the slurry with higher w/c ratio. Therefore, increasing the amount of KMnO4 catalyst under high w/c ratio is more helpful for the foaming effect than under low w/c ratio. The pores in cement slurry with KMnO4 catalyst are more regular and the slurry with catalyst possesses higher porosity than the control group.